2016
DOI: 10.1159/000447978
|View full text |Cite
|
Sign up to set email alerts
|

Internal Carotid Artery S-Shaped Curve as a Marker of Fibromuscular Dysplasia in Dissection-Related Acute Ischemic Stroke

Abstract: Background and Purpose: Craniocervical fibromuscular dysplasia (FMD) is associated with dissections and with S-shaped curves in the internal carotid artery (ICA). We evaluated the occurrence of S-curves in patients presenting with acute strokes due to ICA steno-occlusive dissections. Methods: This was a retrospective review of the interventional databases of two academic tertiary-care institutions. The presence of ICA S-shaped curves, C-shaped curves, 360-degree loops, as well as classic FMD and atheroscleroti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…15,16 This tortuosity pattern (the S-shaped curve) has been described in fibromuscular dysplasia and highly associates with carotid dissection. 17,18 Arterial tortuosity has also been reported in the Loeys-Dietz syndromes especially on vertebral arteries, but it is not specific to vEDS and we found a low prevalence in our cohort.…”
Section: Clinical and Population Sciencescontrasting
confidence: 43%
“…15,16 This tortuosity pattern (the S-shaped curve) has been described in fibromuscular dysplasia and highly associates with carotid dissection. 17,18 Arterial tortuosity has also been reported in the Loeys-Dietz syndromes especially on vertebral arteries, but it is not specific to vEDS and we found a low prevalence in our cohort.…”
Section: Clinical and Population Sciencescontrasting
confidence: 43%
“…DAVFs are characterized by abnormal arteriovenous shunts on the dura mater, but those of the hypoglossal canal (HCDAVFs), are classified as ventral-type fistulas according to Lasjaunias' classification with fibromuscular dysplasia (FMD). 3,4) FMD is a vascular lesion typically characterized by the "string of beads sign," which reflects stenosis and dilation of the ICA, or long tubular stenosis. One study reported that the incidence of S-shaped ICA in patients with FMD was higher than in healthy adults.…”
Section: Discussionmentioning
confidence: 99%
“…2) Furthermore, another study indicated that dissection of the ICA was frequently observed when bilateral S-shaped ICAs were detected on cerebral angiography in patients with acute ischemic strokes. 3) FMD is common in women aged 40-60 years. Our patient was male, but the presence of FMD as a background factor was suggested.…”
Section: Discussionmentioning
confidence: 99%
“…1c). 3 Although antihypertensive treatment was initiated, her blood pressure was difficult to control; we therefore performed additional tests to determine its cause. Magnetic resonance angiography revealed left renal artery stenosis (Fig.…”
Section: Figmentioning
confidence: 99%